Analisis Perbandingan Model Altman, Springate, Ohlson, Fulmer, CA-Score dan Zmijewski Dalam Memprediksi Financial Distress (studi empiris pada Perusahaan Food and Beverages yang Terdaftar di Bursa Efek Indonesia Periode 2010-2012) - Veronita Wulandari; Emrinaldi Nur Dp; Julita ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study purpose to determine wheter there are differences among Altman model, Springate model, Ohlson model, Fulmer model, CA-Score model and Zmijewski model to predict financial distress, and to find out which the Financial Distress prediction model has the most excellent implementation on food and beverages company in indonesia. Comparison of those six models were made by analyzing the accuracy of each model, by using the real condition of a company's net income.The data used in the form of annual financial statements published by the company on the Indonesia Stock Exchange website. The population used is a Food and Beverages companies listed on the Indonesia Stock Exchange period 2010-2012. The sampling technique is purposive sampling with a total sample obtained by 12 companies. In this study will be used t test, additional testing is done to see the feasibility of the model by observing the F test results and test the coefficient of determination (R2), R2 value used to examine differences among Altman, Springate, Ohlson, Fulmer, CA-Score and Zmijewski models in predicting financial distress.The results from this research showed that any prediction model used in this study can be used to predict Financial Distress, except CA-Score models that have significant value t test and F-test is greater than the probability and the value can be inferred CA-Score models can not be used to predict corporate Financial Distress. The results also showed that the most accurate model is the model Ohlson. At the end of the study was to try predict 12 firms sample used listed on the Stock Exchange with Ohlson model. Predicted results showed that five companies are expected to experience Financial Distress in the future.Keywords: Financial Distress, Prediction Models, Financial Ratio, financial statement